The Explorative Analysis to Revise Fear Network Model for Panic Disorder: Functional Connectome Statistics - Lai, Chien-Han (Medicine (Baltimore), 2016)
Functional connectome analysis in panic disorder (PDO) is a relatively new field for research. We tried to investigate the functional connectome alterations in PDO to re-examine the precision and role of fear network model for the pathophysiology of PDO. We enrolled 53 PDO patients and 54 controls with imaging data in this study. After preprocessing, we calculated the connectivity matrix of functional connectivity in whole brain for each subject. Then network-based statistics (The University of Melbourne and Melbourne Health, Australia) of connectome was used to perform group comparisons between patients and controls. The correlation between network measures of significant subnetwork and illness duration or severity of PDO was also performed. Within the 6 network models, only 1 network survived after multiple corrections. We found decreased functional connectivity in the edges between the following nodes: the left parahippocampal gyrus, bilateral precentral gyri, bilateral middle cingulate gyri, bilateral supramarginal gyri, bilateral calcarine fissures, and right lingual gyrus. The central hubs were the left parahippocampal gyrus and left precentral gyrus. The importance of limbic areas and connection with sensory and motor regions might shed light on the revision of fear network model for the pathophysiology of PDO.